Exploring psychosocial needs of young women with breast cancer in a country with crisis: a mixed-methods study - SHAZA, HASAN; Chew, Keng Sheng; Rekaya Vincent, Balang; Shirly Wong, Siew Ling (Malaysian Medical Association (MMA), 2025)
Introduction: Previous research conducted in politically stable countries showed that the diagnosis and treatment of breast cancer among young women can be very distressing and devastating and may result in a lot of unmet psychosocial needs affecting their quality of life. This study aimed to address the psychosocial needs of young women with breast cancer in war-torn Syria.